Urban Land Systems: An Ecosystems Perspective - Andrew Millington (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Global urbanization creates challenges towards sustainability and human well-being. Urban areas are dependent on the ecosystems beyond the city limits but also benefit from the internal urban green places. An understanding of the importance of urban ecosystem services means that urban greenery can be designedly maintained or even expanded. As cities are expected to grow at a rapid rate in the coming decades, it is important that the ecosystem perspective is understood and valued by city planners and political decision-makers. This special issue highlights some aspects related to urban sprawl dynamics and urban ecosystem management. Observations and studies presented in ten papers show that urbanization affects essential ecological, economic, and social landscape functions, whose importance is often undervalued in cities worldwide.